Transforming technologies to manage our information : the future of personal information management. Part 2 - Jones, William P., 1952- (San Rafael, California : Morgan & Claypool, 2014)
With its theme,'Our Information, Always and Forever,' Part I of this book covers the basics of personal information management (PIM) including six essential activities of PIM and six (different) ways in which information can be personal to us. Part I then goes on to explore key issues that arise in the'great migration' of our information onto the Web and into a myriad of mobile devices. Part 2 provides a more focused look at technologies for managing information that promise to profoundly alter our practices of PIM and, through these practices, the way we lead our lives.
5. Technologies of input and output -- 5.1 Technologies of output -- 5.2 Technologies of input -- 6. Technologies to save our information -- 6.1 The possibility of'total capture' -- 6.2 Personal potentials of a lifelog -- 6.3 Caveats and disclaimers -- 6.4 The PIM transformed, the PIM that remains -- 7. Technologies to search our information -- 7.1 Why don't we use search more often? (and how we may anyway) -- 7.2 Personal potentials of situated searching -- 7.2.1 Search as a relationship -- 7.2.2 Are we talking about personalized search or the search for personal information? -- 7.2.3 What to do with information that seems useful... only not now? -- 7.3 Caveats and disclaimers -- 7.4 The PIM transformed, the PIM that remains -- 7.4.1 Finding/re-finding -- 7.4.2 Keeping -- 7.4.3 The meta-level reach of search -- 7.4.4 Maintaining and organizing -- 7.4.5 Managing privacy and the flow of information -- 7.4.6 Measuring and evaluating -- 7.4.7 Making sense of and using the information -- 7.4.8 The technology remaining -- 8. Technologies to structure our information -- 8.1 Structure, structure everywhere nor any bit to share -- 8.2 Personal potentials of shared structure -- 8.2.1 Visions of the semantic web -- 8.2.2 From the public to the personal -- 8.2.3 Unfulfilled promises -- 8.2.4 More specific, more applied, in-line,'smaller' yes; but simpler? -- 8.2.5 Personal potential revisited: the meaningful sharing of structure -- 8.3 Caveats and considerations -- 8.3.1 Consideration #1: what is the smallest unit for a'meaningful' sharing of structure? -- 8.3.2 Consideration #2: how much meaning can be shared (reliably, usefully) through structure? -- 8.3.3 Consideration #3: how much needs to be the same for structures to be shared? -- 8.3.4 Consideration #4: how much needs to change for structures to be shared? -- 9. PIM transformed and transforming: stories from the past, present, and future -- 9.1 How much'clerical tax' do we pay? -- 9.2 Toward a synthesis of the senses of personal information and the activities of PIM -- 9.3 Personal information management, then and now -- 9.4 Tax-free PIM? -- 9.5 Where do we'PIM' in 2057? -- 9.6 Concluding thoughts on transforming technologies -- References -- Author biography.
Part of : Synthesis digital library of engineering and computer science.
Includes bibliographical references : (pages 129-153).
Keywords: Personal information management